(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
One of the meanings of gallery is that of a place for the exhibition of works of art. In turn, a work of art is a creation, as an aesthetic proposal, contained in a discourse and style that makes use of its own materials, for example, painting or sculpture. On this occasion, the Gallery section of the journal Mayéutica revista científica de humanidades y artes aims to contain, as part of the homage to the figure of Juan Francisco Sans, that which he systematically allowed himself to produce in the field of musicology, and is vast in itself. Its usefulness and relevance make it an impossible reference point to avoid, and perhaps "all roads" lead to it. This updated contribution was kindly provided by his spouse, Mariantonia Palacios. The exhibition is divided into three rooms: Room 1: In memoriam; Room 2: Biography; Room 3: The elegance of a legacy.